The influence of treatment, age at onset, and metabolic control on height in children and adolescents with type 1 diabetes—A SWEET collaborative study. Issue 8 (10th October 2018) - Svensson, Jannet; Schwandt, Anke; Pacaud, Daniele; Beltrand, Jacques; Birkebæk, Niels H.; Cardona‐Hernandez, Roque; Casteels, Kristina; Castro, Sofia; Cherubini, Valentino; Cody, Declan; Fisch, Naama; Hasnani, Dhruvi; et al.
Abstract : Objective: To describe the association between height, demographics, and treatment in youths with type 1 diabetes participating in an international network for pediatric diabetes centers (SWEET). Methods: Data were collected from 55 centers with documented patients' height. All subjects below 20 years of age, diabetes duration >1 year, and without celiac disease were included. World Health Organization growth charts were used to calculate height and body mass index z‐scores. Multiple hierarchic regression models adjusting for known confounders were applied. Results: Data on 22 941 subjects (51.8% male) were analyzed with a median and interquartile range for age 14.8 years (11.2, 17.6), diabetes duration 5.6 years (3.1, 8.9), and height z‐score 0.34 (−0.37, 1.03). Children were taller in the youngest age groups: adjusted height z‐scores of 0.31 (±0.06) and 0.39 (±0.06), respectively; with shorter diabetes duration (<2 years: 0.36 [±0.06]; 2‐<5 years: 0.34 [±0.06]; ≥5 years: 0.21 [±0.06]) and if they were pump users: 0.35 ± 0.05 vs 0.25 ± 0.05 (>three injections/day and 0.19 ± 0.06 [0‐3 injections daily]), respectively. High hemoglobin A1c (HbA1c) and low to normal weight were associated with a lower height z‐score. Trends were identical in all models except for gender. No gender differences were found except in the final height model where females exhibited higher z‐score than males. Conclusion: For youths treated at centers offering modern diabetes management, major growth disturbances are virtually eliminated. For children with a young age at onset, high HbA1c, injections, and/or non‐intensive diabetes, treatment still requires attention in order to attain normal growth.